The Role of Leadership in Forming Effective Organizational Behavior in Kemberin - Dewi, Dyah Handayani; Nugraha, Rizki Nurul; Dafrosa, Dafrosa (West Science Social and Humanities Studies, 2024)
Leadership not only focuses on directing people to achieve desired results, but also involves understanding work motivation, establishing a positive organizational culture, and improving the performance of organizational members. Effective leadership can improve the motivation and performance of organizational members while establishing a positive work culture. Conversely, leadership that lacks support can lead to a lack of morale and ineffective organizational behavior. The implications are critical to the success and continuity of an organization. The case study method was used in this research to investigate in depth how specific leadership styles influence work culture, motivation, collaboration and performance at Kemberin . This approach provides a comprehensive framework for analyzing and interpreting the data obtained. The purpose of this research is to understand how leadership impacts work culture, motivation, collaboration and performance at Kemberin. It is expected that the results of the study can provide a deep understanding of the importance of the role of leadership in shaping effective patterns of behavior in the organizational environment. The strategic implications of the research findings are expected to help improve organizational performance and efficiency in the Ministry of Industry as well as make a positive contribution to the understanding of leadership concepts globally.